Global and regional vegetation fire monitoring from space : planning a coordinated international effort - Ahern, Frank J. (SPB Academic Pub., 2001)
Introduction Increasing conflagrations of forests and other lands throughout the world during the 1980s and 1990s have made fires in forest and other vegetation emerge as an important global concern. Both the number and severity of wildfires (accidental fires) and the application of fire for land-use change, seem to have increased dramatically compared to previous decades of the twentieth century. The adverse consequences of extensive wildfires cross national boundaries and have global impacts. Fire regimes are changing with climate variability and population dynamics. Satellite remote sensin.